2013
DOI: 10.7326/0003-4819-159-5-201309030-00004
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone Injections for the Carpal Tunnel Syndrome

Abstract: Region of Scania Research and Development Foundation and Hässleholm Hospital Organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 25 publications
2
103
0
12
Order By: Relevance
“…23 A recent randomised controlled trial compared three groups (37 patients each) receiving 80 mg methylprednisolone steroid injection, 40 mg methylprednisolone steroid injection, and placebo and found that steroid injections improved symptom scores at 10 weeks but that there was no difference with placebo at one year. 24 Overall, 75% of the patients had surgery within one year. The results of carpal tunnel injection are reported to be worse for patients with more clinically severe disease, those with diabetes, older people, and where symptoms are permanent or unremitting.…”
Section: Corticosteroid Injectionmentioning
confidence: 99%
“…23 A recent randomised controlled trial compared three groups (37 patients each) receiving 80 mg methylprednisolone steroid injection, 40 mg methylprednisolone steroid injection, and placebo and found that steroid injections improved symptom scores at 10 weeks but that there was no difference with placebo at one year. 24 Overall, 75% of the patients had surgery within one year. The results of carpal tunnel injection are reported to be worse for patients with more clinically severe disease, those with diabetes, older people, and where symptoms are permanent or unremitting.…”
Section: Corticosteroid Injectionmentioning
confidence: 99%
“…11 A recent randomized controlled trial (RCT) also showed that steroid injection provided more benefits than placebo at the 10th week of treatment, but there was no significant difference observed at 1-year follow-up. 12 Only one-third of patients with carpal tunnel syndrome who received steroid injections had longer term benefits 13 and some required an additional 2-3 injections to obtain relief. 13 However, 1 study conducted in Estonia reported that patients who received repetitive steroid injections were more likely to have postoperative symptoms of carpal tunnel syndrome if they eventually opted for surgery.…”
mentioning
confidence: 99%
“…The basis for the application of this treatment is the ability of corticosteroids to reduce swelling, thereby improving the spatial relation between the carpal tunnel and the median nerve and tendons. Some scholars demonstrated that the injection of corticosteroids into the common flexor sheath and flexor pollicis longus tendon sheath can effectively relieve pain of CTS patients, improve functional impairment, and delay the need for surgery [6,17,18,19,20]. Advancements in ultrasonography allow the visualization of the structures of the carpal tunnel, including the median nerve, flexor tendons, and the TCL as well as the structures at risk, including the ulnar artery and the proximal palmar arch.…”
Section: Discussionmentioning
confidence: 99%